2023
DOI: 10.3390/ma16083202
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Preparation Method on the Structural, Morphological and Dielectric Properties of FeNbO4 Ceramics

Abstract: In this work, iron niobate (FeNbO4) was prepared via two processes based on the sol-gel method: colloidal gel and polymeric gel. The obtained powders were submitted to heat treatments at different temperatures based on the results obtained via differential thermal analysis. The structures of the prepared samples were characterized via X-ray diffraction and the morphology was characterized via scanning electron microscopy. The dielectric measurements were performed in the radiofrequency region using the impedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…The FE-SEM images indicate that as x increased from 0 to 0.1, FN was formed as a secondary phase with angular grains consistent with the XRD results. In addition, the grain boundary is clearly visible and there is heterogeneity in the grain size distribution The microstructure of the FN phase in the (1 − x )AgNbO 3 – x FeNbO 4 system is similar to the microstructure obtained in the research by Devesa et al 47 The mapping images of the ANF( x ) ceramics are shown in Fig. 7.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…The FE-SEM images indicate that as x increased from 0 to 0.1, FN was formed as a secondary phase with angular grains consistent with the XRD results. In addition, the grain boundary is clearly visible and there is heterogeneity in the grain size distribution The microstructure of the FN phase in the (1 − x )AgNbO 3 – x FeNbO 4 system is similar to the microstructure obtained in the research by Devesa et al 47 The mapping images of the ANF( x ) ceramics are shown in Fig. 7.…”
Section: Resultssupporting
confidence: 79%
“…in the grain size distribution The microstructure of the FN phase in the (1 − x)AgNbO 3 -xFeNbO 4 system is similar to the microstructure obtained in the research by Devesa et al 47 The mapping images of the ANF(x) ceramics are shown in Fig. 7.…”
Section: Dalton Transactions Papersupporting
confidence: 82%
See 3 more Smart Citations